Nonsteroidal anti‐inflammatory drugs but not aspirin are associated with a lower risk of post‐colonoscopy colorectal cancer. Issue 9 (22nd March 2020) - Cheung, Ka Shing; Chen, Lijia; Chan, Esther W.; Seto, Wai Kay; Wong, Ian C.K.; Leung, Wai K.
Summary: Background: Although nonsteroidal anti‐inflammatory drugs (NSAIDs) reduce colorectal cancer (CRC) risk, their role in preventing post‐colonoscopy CRC (PCCRC) remains undetermined. Aims: To investigate whether NSAIDs reduce PCCRC risk after a negative baseline colonoscopy Methods: This is a retrospective cohort study based on a territory‐wide healthcare database of Hong Kong. All patients (aged 40 or above) who underwent colonoscopies between 2005 and 2013 were identified. Exclusion criteria included CRC detected within 6 months of index colonoscopy, prior CRC, inflammatory bowel disease and prior colectomy. The primary outcome was PCCRC‐3y diagnosed between 6 and 36 months after index colonoscopy. Sites of CRC were categorised as proximal (proximal to splenic flexure) and distal. The adjusted hazards ratio (aHR) of PCCRC‐3y with NSAID and aspirin use (defined as cumulative use for ≥90 days within 5 years before index colonoscopy) was derived by propensity score (PS) regression adjustment of 22 covariates (including patient factors, concurrent medication use and endoscopy centre's performance). Results: Of 187 897 eligible patients, 21 757 (11.6%) were NSAID users. 854 (0.45%) developed PCCRC‐3y (proximal cancer: 147 [17.2%]). NSAIDs were associated with a lower PCCRC‐3y risk (aHR: 0.54, 95% CI: 0.41‐0.70), but not CRC that developed >3 years (aHR: 0.78, 95% CI 0.56‐1.09). The aHR was 0.48 (95% CI: 0.24‐0.95) for proximal and 0.55 (95% CI: 0.40‐0.74) for distal cancer. A duration‐ and frequency response relationship was observed ( P trend  < 0.001). For aspirin, the aHR was 1.01 (95% CI: 0.80‐1.28). Conclusions: Non‐aspirin NSAIDs were associated with lower PCCRC risk after a negative baseline colonoscopy.